2022
DOI: 10.3389/fmars.2022.833089
|View full text |Cite
|
Sign up to set email alerts
|

From Phenotypes to Genotypes and Back: Toward an Integrated Evaluation of Biodiversity in Calanoid Copepods

Abstract: Zooplankton molecular analyses allow for accurate species identification with a proper molecular signature, complementing classic phenotypic-based taxonomy (α taxonomy). For the first time in the Mediterranean Sea, cytochrome oxidase I (COI) gene sequences of calanoid copepods were associated with morphological identification, HD and SEM images, using a fully integrated approach to assess taxonomic diversity. Such method was applied to selected species, generating consensus sequences from the Gulf of Naples (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 76 publications
(91 reference statements)
2
13
0
Order By: Relevance
“…Cyclopoida can be distinguished at species level based on detailed morphological identification (Böttger‐Schnack & Machida, 2011; Heron & Frost, 2000; Paffenhofer, 1993), but validated references are almost absent in public molecular datasets. Our sequences obtained from the GoN specimes showed that COI barcoding can accurately identify also cyclopoids at the species level (98%–100% similarity), as observed for calanoid species (Di Capua et al, 2022). COI barcoding can accurately identify Oncaea species, as discussed in Di Capua et al (2017); in addition, a new reference of O. mediterranea was obtained from a site close to its type locality (Messina; Tyrrhenian Sea).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Cyclopoida can be distinguished at species level based on detailed morphological identification (Böttger‐Schnack & Machida, 2011; Heron & Frost, 2000; Paffenhofer, 1993), but validated references are almost absent in public molecular datasets. Our sequences obtained from the GoN specimes showed that COI barcoding can accurately identify also cyclopoids at the species level (98%–100% similarity), as observed for calanoid species (Di Capua et al, 2022). COI barcoding can accurately identify Oncaea species, as discussed in Di Capua et al (2017); in addition, a new reference of O. mediterranea was obtained from a site close to its type locality (Messina; Tyrrhenian Sea).…”
Section: Discussionsupporting
confidence: 74%
“…For Cladocera, 224 COI reference sequences were downloaded from BOLD and were filtered as above. The alignment included 92 filtered data from BOLD, the E. spinifera sequences from the GoN and one sequence of a calanoid copepod species ( Calanus helgolandicus accession number JX995315.1) as an outgroup (Di Capua et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations